Psychometric Properties of the Chinese Version of Short-Form Community Attitudes Toward Mentally Illness Scale in Medical Students and Primary Healthcare Workers - Tong, Yan; Wang, Zhizhong; Sun, Yan; Li, Shulan (Frontiers in Psychiatry, 2020)
Objective To assess the psychometric properties of the short form Community Attitudes toward Mentally Illness (SF-CAMI) scale among two Chinese samples. Methods Original English version CAMI was translated following a standard procedure. And then short-form CAMI developed through the multistage procedure. The psychometric properties were tested among two separate samples of which content 1,092 primary healthcare workers and 1,228 medical college students. Reliability was assessed using internal consistency reliability and test-retest reliability. Exploratory factor and confirmatory factor analysis were used to assess the structure and validity of the scale. Results The Chinese version SF-CAMI consist of 20-item and with three subscales: Benevolence, Fear and Exclusion and Support and Tolerance. The confirmatory factor analysis indicated a good model fit for these two samples. The Cronbach α of total scale for both samples were good (0.82 for medical college students, and 0.85 for primary healthcare workers), and acceptable test-retest reliability showed in both sample (ICC was 0.62 in medical college students, and 0.60 in primary healthcare workers). Conclusion The Chinese version SF-CAMI performed good reliability and validity among both primary healthcare workers and medical college students, provide more feasible and valid tools for assessing the effect of mental health service programs in China.